89.9k views
19 votes
(a) Rearrange the equation
x
+ 2y = 6 to make y the subject.

2 Answers

6 votes

Answer:


y=3-(x)/(2)

Explanation:

1. Examine Equation

x+ 2y = 6

2. Subtract "x" from both sides

2y = 6-x

3. Divide both sides by 2


y = (6)/(2) -(x)/(2)

4. Simplify


y=3-(x)/(2)

User Nominolo
by
6.2k points
8 votes

To make y the subject, we must move everything to one side and y on the other.


x + 2y = 6\\2y = 6 -x\\2y = -x + 6\\y =-(1)/(2) x + 3

Good day and I hoped that helped!

User M Gholami
by
5.7k points